Pengembangan Scrapbook Digital Berbasis Audiovisual Materi Keberagaman Kebudayaan di Indonesia untuk Siswa Kelas IV di SD Negeri 17 Pangkalpinang - Zeni Sagita; Maulina Hendrik; Diana Pramesti (Universitas Muhammadiyah Bangka Belitung, 2023)
This research is motivated by the less optimal use of learning media in teaching and learning activities. The lack of teacher innovation and creation in making media makes students less enthusiastic about participating in learning. Therefore, it is necessary to innovate learning media based on questionnaire answers, analyzing student needs, observing, interviewing the characteristics of fourth grade students. This study aims to develop audiovisual-based digital scrapbook media material for cultural diversity in Indonesia for fourth grade students at SD Negeri 17 Pangkalpinang, valid and practical. The type of research used is Research and Development (R&D) with the ADDIE model, namely the Analysis, Design, Development, Implementation, Evaluation stages. Data collection techniques are observation, interviews, learning outcomes tests and questionnaires. Data analysis used descriptive quantitative and qualitative data. The research results obtained were media expert I the final result was 100%, media expert II was 86%, media expert III was 88%